7 Does the level of a negative 1st round fit predict subsequent pathology in a colorectal cancer screening programme?. (5th April 2017) - Gibson, DJ; Mooney, T; Mooney, J; O'Donoghue, D
Abstract : Background: BowelScreen is based on faecal immunohistochemistry test (FIT); current threshold for positive FIT is 225 ng Hb/mL. During 1st round of screening referral rate for colonoscopy is 5%. Concerns for a higher cut-off compared to some other screening programmes are that significant pathology could be missed but this has to be balanced against overstretched endoscopy departments. Aim: To examine patients who initially have a negative FIT, which subsequently becomes positive in the second round, and correlate quantitative initial FIT to pathology encountered. Method: Retrospective review of all patients with a negative 1st round FIT subsequently becoming positive was performed. In BowelScreen, surveillance interval for adenomas detected is based on ESGE guidelines, categorising patients as high risk intermediate risk or low risk. For this study, 'advanced pathology' (AP) was classified as cancer high risk and intermediate risk adenomas. The initial negative FIT values were divided into 4 groups: 0 (group 1), 1-75 (group 2), 76-150(group 3) and 151-225ng Hb/mL(group 4). Results: 488715 individuals were screened in round 1, 95% of whom had a negative FIT. 3.6% were FIT positive in round 2;295 have proceeded to colonoscopy.38 patients had an initial FIT in group 1208 in group 2, 31 in group 3 and 18 in group 4.70 patients (24%) were classed as AP(CRC n=16, high risk polyps n=10, medium risk polyps n=44), while 225 (76%)had NAP. We observed a stepwise increase in amount of AP encountered with increasing initial FIT. Group 1:4/38 (11%); group 2:50/208 (24%); group 3:10/31 (32%); group 4 6/18 (33%).When grouped as a whole, the median initial FIT for AP was 40 vs17ng Hb/mL for NAP(p<0.0001).Initial negative FIT was a better predictor of AP than the 2nd round positive FIT. Conclusions: There is a clear correlation between level of FIT and pathology encountered, even when the FIT is negative.